sTREM-1 is elevated in cystic fibrosis and correlates with proteases - Forrester, D.L.; Barr, Helen L.; Fogarty, Andrew W.; Knox, A. (Wiley, 2017)
Background: sTREM-1 (soluble triggering receptor expressed on myeloid cells-1) is a novel inflammatory marker that may be of clinical use in cystic fibrosis (CF). Dysregulation of the TREM pathway has been demonstrated in other inflammatory diseases and modulation in animal models has therapeutic benefit. We hypothesised that sTREM-1 could act as a biomarker of disease in cystic fibrosis.